PERANCANGAN DESAIN PUSAT PELATIHAN TIM NASIONAL SEPAKBOLA INDONESIA - Rasyad Firzatila; Timmy Setiawan (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
As one of the countries with the most fans and connoisseurs of football, Indonesia is still lacking in terms of facilities that can support the continuation of the game, this is very unfortunate becauce the Indonesian national team does not have qualified training facilities to train in preparation for international competitions such as AFC Asian Cup. Football training center have an important role in the development of national teams in every country. The training center is used as a place for national team players to practice developing their technical, physical, mentality, and tactical abilities. The Garuda project tries to contribute as a platform and foundation for Indonesian football to continue to grow to reach the goals of all football fans in Indonesia. This project is a specially designed and exclusive football training center for the Indonesian National Football Team. In it, players and coaches can practice preparing technically, physically and mentally in preparation for friendly matches, domestic matches, to international matches. Assisted by the existence of an official office that takes care of all administrative interests of the Indonesian Football National Team. There are 2 football pitches with natural turf and synthetic turf in the football training centre, which comply with FIFA standards. Coupled with other facilities such as a gym area, hydrotherapy pool, physiotherapy area, strategy tactics education class, locker room, indoor court, and dormitory rooms as a complement to all training activities for the Indonesian National Football Team. Keywords:  football; indonesia national team; national training center Abstrak Sebagai salah satu negara dengan jumlah penikmat sepakbola terbanyak, sepakbola di Indonesia masih kurang mumpuni dalam segi fasilitas yang dapat menunjang keberlangsungan permainan, hal ini sangat disayangkan dikarenakan tim nasional Indonesia tidak memiliki fasilitas latihan yang mumpuni untuk berlatih guna persiapan kompetisi internasional seperti AFC Asian Cup. Pusat pelatihan sepakbola memiliki peran yang penting dalam perkembangan tim nasional di setiap negara. Pusat pelatihan dijadikan sebagai wadah untuk para pemain tim nasional untuk berlatih mengembangkan kemampuan teknik, fisik, mental, dan taktik. Proyek The Garuda mencoba berkontribusi sebagai wadah dan pondasi sepakbola Indonesia untuk terus berkembang menggapai cita-cita seluruh penggemar sepakbola di Indonesia. Proyek ini merupakan pusat pelatihan sepakbola yang dirancang khusus dan eksklusif untuk Tim Nasional Sepakbola Indonesia. Di dalamnya dapat digunakan pemain dan pelatih berlatih mempersiapkan teknik, fisik, dan mental untuk persiapan pertandingan persahabatan, pertandingan domestik, hingga pertandingan internasional. Dibantu dengan adanya kantor official yang mengurus segala kepentingan administratif Tim Nasional Sepakbola Indonesia. Terdapat 2 lapangan sepakbola dengan rumput alami dan rumput sintetis di pusat pelatihan sepakbola, yang sesuai dengan standar FIFA. Ditambah dengan fasilitas lain seperti area gym, kolam hidroterapi, area fisioterapi, kelas edukasi taktik strategi, ruang ganti, lapangan indoor, dan kamar asrama sebagai pelengkap segala kegiatan pelatihan Tim Nasional Sepakbola Indonesia.